THE UNIQUENESS OF DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE TEACHERS BASED ON THE EDUCATIONAL PROCESS - Atabek Sotbarov; Dilfuza Sotbarova (European Science Publishing, 2024)
There was talk about the uniqueness of developing the professional competence of future teachers based on the educational process.
Keywords: Pedagogy, education, training, competence, thinkers, technology, method, educational process.